Empreendedorismo e família: quando flexibilizar horários se torna uma sobrecarga para as mulheres - Tanure, Paula Torres (2014)
Women’s entrepreneurship, as a considerably new field in company administration, still receives little attention from this area, especially when regarding national publications. The increasing number of women entering entrepreneurship also awakens the interest in knowing what motivated them to undertake this kind of work and the reality of these women who face double or even triple working hours. The search for schedule flexibility in order to spend more time with family leads these women to opting for self-employment as a means of work. This study aimed at analyzing if women’s choice for entrepreneurship is related to the need of conciliating work and family. For the data collection we performed interviews with entrepreneur women of the city of São Paulo and adjacent cities. The interviews showed that they are motivated to entrepreneurship in order to have more time with family, however, in counterpoint, they face work overload. Despite having more time with family, they also long for the development of the business.